Reduced version of the scale of attitudes towards alcohol, alcoholism, and alcoholics: primary results - Vargas, Divane de (Revista da Escola de Enfermagem da USP, 2011)
This study aimed to analyze the items of the Scale of Attitudes toward Alcohol, alcoholism and alcoholics in order to prepare a reduced version keeping the instrument's psychometric properties. The preliminary version of the Scale composed by 165 items was tested in a sample with 144 nursing student. The evaluation process of the items consisted of the total-item coefficient correlation and reliability of the instrument was estimated by Cronbach's alpha coefficient. Results indicate the permanence of 83 items, divided into five factors that showed satisfactory values in the different coefficients of internal consistency. Further studies are needed with larger samples in order to give continuity to the process of scale validation among health professionals.